FAKTOR - FAKTOR YANG MEMPENGARUHI PERMINTAAN RUMAH DI INDONESIA - Yuli Afmi Afika; Ariusni Ariusni (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This research aims to examine the factors that influence the demand for houses in Indonesia with the selected model is the Fixed Effect Model (FEM). The data used is panel data during the period 2013-2017, with the technique of collecting documentation data and library studies obtained from relevant institutions and agencies. The variables use are income, population, marriage, and inflation. The research method used is Ordinary Least Square (OLS). The estimation results show that income, marriage and inflation have a positive and significant effect on the demand for housing in Indonesia. Meanwhile simultaneously income, marriage and inflation affect the demand for housing in Indonesia.